Os quilombos e seus direitos hoje: entre a construção das identidades e a história - French, Jan Hoffman (Revista de História, 2003)
This article illustrates that new concepts of quilombo, arising from the process of legal recognition, reconfigure identities through a dialogue between history, law, and cultural practices in a community in the sertão of Sergipe. It challenges dichotomous theorizations that juxtapose essentialized racial identity against instrumental ethnic identification for the purpose of gaining land and resources.